2021
DOI: 10.3390/su13094601
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing Eco-Sustainable Products: Interrelationship between Environmental Knowledge, Environmental Concern, Green Attitude, and Perceived Behavior

Abstract: Due to eco-sustainable marketing practices, customer consciousness has increased the use of eco-sustainable goods in India. This provides new opportunities for businesses and researchers in terms of eco-sustainable behavior; however, the market analysis in India is weak. This study examines the factors that trigger consumers to purchase eco-sustainable products and the interrelationship between environmental knowledge (EK), environmental concern (EC), green attitude (GA), and perceived behavior control (PB) am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 54 publications
(108 reference statements)
8
50
0
1
Order By: Relevance
“…Further, studies showed that environmental concern drives the desire to seek environmental knowledge of issues and procedures (Okumus et al, 2019; Rusyani et al, 2021). When people get worried about the situation of the environment and want to contribute to the solution, they will seek out the knowledge in ensuring that they can effectively contribute to environmental sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, studies showed that environmental concern drives the desire to seek environmental knowledge of issues and procedures (Okumus et al, 2019; Rusyani et al, 2021). When people get worried about the situation of the environment and want to contribute to the solution, they will seek out the knowledge in ensuring that they can effectively contribute to environmental sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it is critical to emphasize that environmental knowledge was positively associated with customers' environmental attitudes (Anbukarasi & Dheivanai, 2017). The better-informed visitors were about an environmental issue, the more their attitudes shifted toward environmental consciousness, which directly affects their willingness to purchase eco-friendly items and engage in green purchasing behavior (Rusyani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, although aspects such as “healthiness” and “environmental friendliness” are attributes that are considered by consumers at the time of purchase, they may not automatically be reflected into their concrete action [ 23 ]. Indeed, understanding consumers’ behavior is a necessary prerequisite for effective marketing [ 24 ]. Therefore, companies could help people make healthy and environmentally friendly choices by communicating these issues more effectively and truthfully through packaging design, packaging images and labels.…”
Section: Introductionmentioning
confidence: 99%